Digital image correlation vibrometry with low speed equipment - Warburton, J.R.; Lu, G.; Buss, T.M.; Docx, H.; Matveev, Mikhail Y.; Jones, I.A. (Springer, 2016)
A low-cost method is presented which enables digital image correlation (DIC) with conventional cameras (i.e. not high-speed) to be used for determination of vibration deflected shapes via the use of a stroboscopic lamp and some simple ancillary circuits. For each natural frequency of the structure under consideration, a sequence of images is captured asynchronously with the vibrations using the DIC system and the resulting displacement fields are correlated with the excitation signal driving the vibration using a least-squares approach. Three approaches for performing this correlation are outlined, one of which is developed into the algorithm used for processing the present results to obtain the amplitude and phase of the vibration at each point on the specimen, allowing the deflected shape to be reconstructed. This process is illustrated using the example of a vibrating aluminium plate. The resulting shapes and frequencies agree well with finite element modal analyses of the plate.